In Salzburg about Europe in the 90s (Czech Journal of International Relations, 1992)
The Salzburg Seminar is an American center for interdisciplinary dialogue and education, founded in 1947. Every year it organizes a number of thematically focused discussions with the participation of prominent experts and politicians.The main leaders of the 290th seminar (May 5-17, 1991) were Herbert S. Okun, executive director of the Financial Service Volunteer Corps, long-time US diplomat, former ambassador to the GDR and deputy head of the US delegation at the SALT II negotiations, and Leo Tindemans , member of the European Parliament and former Prime Minister and then Minister of Foreign Affairs of Belgium.The discussed questions can be roughly divided into four areas.I. General problems of international relationsII. Problems of Central Eastern EuropeIII. Development in countries in the WestIV. Solution options